Tracheobronchial foreign bodies in children – a retrospective study of 2,000 cases in Northwestern China - Liang JM; Hu J; Chang HM; Gao Y; Luo HN; Wang ZH; Zheng GX; Chen F; Wang T; Yang YY; Kou XH; Xu M (Dove Medical Press, 2015)
Jianmin Liang,1 Juan Hu,1 Huimin Chang,2 Ying Gao,1 Huanan Luo,1 Zhenghui Wang,1 Guoxi Zheng,1 Fang Chen,1 Ting Wang,1 Yeye Yang,1 Xiaohui Kou,1 Min Xu1 1Department of Otolaryngology-Head and Neck Surgery, The Second Hospital, Xi’an Jiaotong University, 2Department of Otolaryngology-Head and Neck Surgery, Affiliated Hospital of Xi’an Medical University, Xi’an, People’s Republic of China Abstract: The aim of this study is to report our experience in the diagnosis and treatment of tracheobronchial foreign bodies (TFBs). We retrospectively reviewed medical records of 2,000 TFB patients (1,260 males and 740 females) who were treated between January 2010 and December 2013. Chest radiography and computed tomography were performed to diagnose TFBs. The location and type of foreign bodies (FBs), anesthesia methods, and treatment outcomes and complications were analyzed. Overall, 72.5% of our patients with TFB were aged between 1 years and 3 years. Plant-based FBs are the most common FB type, accounting for 91.5%. Almost 52.1% of the FBs were encountered in the right bronchus. The coincidence rate for computed tomography-based three-dimensional reconstruction was significantly greater than that for chest X-ray examination (98.7% vs 82.0%, P<0.01). Under general anesthesia, the FBs were removed by rigid bronchoscopy. Neither anesthesia complication nor intraoperative hypoxemia occurred. There were seven deaths from acute obstructive asphyxia and eight from residual FB-induced chronic asphyxia and respiration-circulation failure. In conclusion, early diagnosis and prompt treatment of TFBs with rigid bronchoscopy under general anesthesia is effective in reducing complications and mortality in affected children. Keywords: respiratory tract foreign body, children, diagnosis, treatment